Comparison on phytochemical constituents in the patchouli oil of in vitro and ex vitro pogostemon cablin leaves - Wan Nurul Hidayah, W. A.; Putri Shareen, R.; Nur Atirah, H.; Tan, Suat Hian (Universiti Teknologi Mara, 2021)
Pogostemon cablin (patchouli) is a medicinal herb well known for its essential oil derived from the leaves. Patchouli oil shows excellent base note in fragrance industries for its fixatives properties and its patchouli alcohol (patchoulol) is used as quality indicator for its oil. However, the P. cablin is the only commercial source of patchoulol and cannot be obtained synthetically in the laboratory. Higher demand in the production of its essential oil gave a significant contribution for in vitro grown P.cablin to meet the market supply for industries. Hence, in this study, the essential oil in both in vitro and ex vitro P.cablin were extracted from its leaves by means of hydrodistillation method and its phytochemical constituents were identified and compared using Gas Chromatography Mass Spectrometry. The yield and quality of its essential oil from both in vitro and ex vitro P.cablin’s leaves were investigated. In vitro patchouli essential oil extraction gaves higher yield (40 ml) than the ex vitro patchouli essential oil (26 ml) under similar condition for hydrodistillation. Six major components were identified through GC-MS and was compared between two samples which are β- patchoulene, Caryophyllene, α- guaiene, α- cedrene, α- bulnesene and Patchouli alcohol. The patchoulol, which is the main constituents that is important in fixative had doubled (42.18 %) in the in vitro P.cablin essential oil compared to ex vitro (29.24%). This finding was reflected based on the peak area percentage of each substance through GC-MS. Other constituents in the in vitro P.cablin were found still competitive to the ex vitro in slightly lower values. Overall, in vitro P.cablin showed higher yield and quality compared to the ex vitro grown P.cablin.